Production of a Bose-Einstein condensate of sodium atoms and investigation considering non-linear atom-photon interactions - Peñafiel, Edwin Eduardo Pedrozo (2016)
In this work we constructed an experimental system to realize a BEC of sodium atoms. In the first part of the work, we study two atomic sources in order to choose the most suitable for our system. The comparison between a Zeeman slower and a bidimensional magnetooptical trap (2D-MOT) was performed to evaluate the capacity of producing an appropiate flux of atoms in order to load a tridimensional magneto-optical trap (3D-MOT). The experimental results show that the 2D-MOT is as efficient as the Zeeman slower with the advantage of being more compact and easier to operate, and for these reasons we choose it as our source of cold atoms. After this, the experimental apparatus to produce a Bose-Einstein condensate was constructed and characterized. With this experimental system we realized all the required stages to achieve the Bose-Einstein condensation (BEC). Initially, we characterized and compared the performance between the Bright-MOT and Dark-SPOT MOT of sodium atoms, observing the great advantages this last configuration offers. Afterward, we implemented the experimental sequence for the achivement of the BEC of sodium atoms. After the optical molasses process, the atoms are tranferred to an optically plugged quadrupole trap (OPT) where the process of evaporative cooling is performed. With this setup, we achive a sodium BEC with ∼ 5×105 atoms and a critical temperature of ∼ 1.1 μK. Finally, with the constructed and characterized machine, we started to perform experiments of cooperative absorption of two photons by two trapped atoms. With the new system, we wanted to take advantage of the higher densities in the magnetic trap and BEC to explore some features of this phenomenon in the classical and quantum regimes. We were interested in exploring some features of this nonlinear light-matter interaction effect. The idea of having two or more photons interacting with two or more atoms is the beginning of a new possible class of phenomena that we could call many photons-many body intercation. In this new possibity, photons and atoms will be fully correlated, introducing new aspects of interactions.